Characterization of Rubella Seronegative Females in the Zambian Blood Donor Community - Mazaba, Mazyanga L.; Monze, Mwaka; Babaniyi, Olusegun A.; Siziya, Seter; Michelo, Charles (Frontiers in Public Health, 2015)
Rubella is an acute, contagious viral infection caused by a teratogenic enveloped single-stranded RNA virus, rubella virus, a member of the togaviridae family. Though causing generally mild infections in children and adults, it is a disease of public health importance in pregnant women causing major problems including abortions, miscarriages and Congenital Rubella Syndrome in more than twenty per cent of the susceptible population. This study was carried out to determine the characteristics associated with rubella seronegativity amongst female blood donors in Zambia. Rubella-specific IgG antibody levels were measured in the blood serum. Proportions were compared using the Chi-squared test at the 5% significance level, and magnitudes of associations were determined using the odds ratio and its 95% confidence interval. Of the 124 female blood donors tested for rubella IgG 46.0% were aged less than 20 years. Overall, 66.7% of the participants had never been married. More than half (62.1%) of the participants resided in rural areas of the country. Of the 114 participants with recorded level of education, 50.1% had at–least completed secondary school. Out of 43 participants with recorded current employment status, 44.2% were not working for pay. A total of 10 (8.1%) participants were sero-negative to rubella IgG antibodies. No factors were associated with seronegativity. Protection against rubella through natural infection appears inadequate to protect the population, increasing the risk of CRS.